Reliability of a New Arthroscopic Discoid Lateral Meniscus Classification System: A Multicenter Video Analysis. Issue 5 (April 2022) - Lee, R. Jay; Nepple, Jeffrey J.; Schmale, Gregory A.; Niu, Emily L.; Beck, Jennifer J.; Milewski, Matthew D.; Finlayson, Craig J.; Joughin, V. Elaine; Stinson, Zachary S.; Pace, J. Lee; ,; Albright, Jay; et al.
Background: The discoid lateral meniscus (DLM) is one of the most common congenital anomalies of the knee. The pathomorphology of DLM varies. Current classification systems are inadequate to describe the spectrum of abnormality. Purpose: A study group of pediatric orthopaedic surgeons from 20 academic North American institutions developed and tested the reliability of a new DLM classification system. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: After reviewing existing classifications, we developed a comprehensive DLM classification system. Four DLM features were evaluated: meniscal width, meniscal height, peripheral stability, and meniscal tear. Stepwise arthroscopic examination using anteromedial and anterolateral viewing portals was established for evaluating these features. Three senior authors who were not observers selected 50 of 119 submitted videos with the best clarity and stepwise examination for reading. Five observers performed assessments using the new classification system to assess interobserver reliability, and a second reading was performed by 3 of the 5 observers to assess intraobserver reliability using the Fleiss κ coefficient (fair, 0.21-0.40; moderate, 0.41-0.60; substantial, 0.61-0.80; excellent, 0.81-1.00). Results: Interobserver reliability was substantial for most rating factors: meniscal width, meniscal height, peripheral stability, tear presence, and tear type. Interobserver reliability was moderate for tear location. Intraobserver reliability was substantial for meniscal width and meniscal height and excellent for peripheral stability. Intraobserver agreement was moderate for tear presence, type, and location. Conclusion: This new arthroscopic DLM classification system demonstrated moderate to substantial agreement in most diagnostic categories analyzed.